The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-61209-6
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization with medium-sized doxorubicin-eluting Callisphere is safe and effective for patients with hepatocellular carcinoma

Abstract: the study aimed to compare the tumor response to and complications of doxorubicin-eluting calliSphere bead-transarterial chemoembolization (DeB-tAce) using small-and medium-sized beads in patients with hepatocellular carcinoma (Hcc) who underwent multiple rounds of oncology therapies. Sixty patients with intermediate stage HCC who had previously received multiple oncology therapies underwent DEB-TACE with CalliSpheres of 100-300 μm (small bead group, n = 34) or 300-500 μm (medium bead group, n = 26) in diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Many pieces of research have proved that it can load more kinds of chemotherapy drugs and has a higher drug-loading efficiency compared with other DEBs [7][8][9]. According to several recent studies, unresectable HCC patients who receive DEB-TACE treatment using CSM have better treatment response, prolonged overall survival (OS) and reduced adverse events (AEs) compared with cTACE [10][11]. Therefore, the purpose of this study was to investigate the treatment efficacy and safety of DEB-TACE using CSM and to identify important prognostic factors related to the survival of HCC patients with PVTT.…”
Section: Introductionmentioning
confidence: 99%
“…Many pieces of research have proved that it can load more kinds of chemotherapy drugs and has a higher drug-loading efficiency compared with other DEBs [7][8][9]. According to several recent studies, unresectable HCC patients who receive DEB-TACE treatment using CSM have better treatment response, prolonged overall survival (OS) and reduced adverse events (AEs) compared with cTACE [10][11]. Therefore, the purpose of this study was to investigate the treatment efficacy and safety of DEB-TACE using CSM and to identify important prognostic factors related to the survival of HCC patients with PVTT.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the pharmacokinetic profile revealed the speed of drug‐eluting, which is critical to the treatment efficacy of TACE. Many studies compare the embolic particles with different sizes, such as 100–300 versus 700–900 μm, 100–300 versus 300–500 and 500–700 μm, 100–300 versus 300–500 μm, and 70–150 versus 100–300 μm (Namur et al, 2010; Padia et al, 2013; Prajapati et al, 2014; Wang et al, 2020). A preliminary study found that the DOX‐loaded LC/DC Beads with 100–300 μm size employed a higher necrosis rate than 700–900 μm beads.…”
Section: Microspheresmentioning
confidence: 99%
“…Therefore, it is essential that the embolic microsphere has a suitable diameter for TACE, which is based on blood vessel size. The size of microspheres used for TACE in clinical trials has ranged from 50 to 500 µm [33]. To evaluate the size variation in the GG and GG/AFGO-Dox microspheres, their diameter was measured using a laser diffraction particle size analyzer.…”
Section: Synthesis and Characterization Of Gg And Gg/afgo-dox Microspheresmentioning
confidence: 99%